A Simple Sinusoidal Buck Converter Working as A Single-Phase Grid-Connected Inverter - Hanny H. Tumbelaka (Institute of Research and Community Outreach - Petra Christian University, 2021)
The need for a simple grid-connected inverter is increasing. The integration of a simple buck converter and a push-pull converter to be a grid-connected inverter is presented in this paper. The buck converter is controlled by a sinusoidal duty ratio to produce a series positive half-cycle of a sine wave. Then, the push-pull converter solves it to generate the complete sinusoidal output voltage and current. Moreover, grid synchronization works properly by sensing the grid voltage, which is then used as a reference voltage to connect the inverter to the grid successfully. The grid sees the inverter as a resistive load with a unity power factor. The total harmonic distortion (THD) of the grid current is 4.87% for the THD grid voltage of 2.07%.